Loss of sexual reproduction and dwarfing in a small metazoan. - Claus-Peter Stelzer; Johanna Schmidt; Anneliese Wiedlroither; Simone Riss (PLoS ONE)
Background Asexuality has major theoretical advantages over sexual reproduction, yet newly formed asexual lineages rarely endure. The success, or failure, of such lineages is affected by their mechanism of origin, because it determines their initial genetic makeup and variability. Most previously described mechanisms imply that asexual lineages are randomly frozen subsamples of a sexual population. Methodology/principal findings We found that transitions to obligate parthenogenesis (OP) in the rotifer Brachionus calyciflorus, a small freshwater invertebrate which normally reproduces by cyclical parthenogenesis, were controlled by a simple Mendelian inheritance. Pedigree analysis suggested that obligate parthenogens were homozygous for a recessive allele, which caused inability to respond to the chemical signals that normally induce sexual reproduction in this species. Alternative mechanisms, such as ploidy changes, could be ruled out on the basis of flow cytometric measurements and genetic marker analysis. Interestingly, obligate parthenogens were also dwarfs (approximately 50% smaller than cyclical parthenogens), indicating pleiotropy or linkage with genes that strongly affect body size. We found no adverse effects of OP on survival or fecundity. Conclusions/significance This mechanism of inheritance implies that genes causing OP may evolve within sexual populations and remain undetected in the heterozygous state long before they get frequent enough to actually cause a transition to asexual reproduction. In this process, genetic variation at other loci might become linked to OP genes, leading to non-random associations between asexuality and other phenotypic traits.